O letramento na síndrome de down : o papel da família e da escola - Feistauer, Cláudia Madalena (2014)
In a society of literate culture, where reading is valued, not understanding the written materials to circulate socially means to live in a parallel world. So, reading and writing become the way of access to social inclusion, since they constitute fundamental learnings for individuals to be inserted in societies considered literates. Nevertheless, it is important to recognize not only the domain of the code of reading and writing, but also the competence as a reader and writer of his own text, his own story, here also including those with special educational needs such as people with Down syndrome. However, studies on literacy these individuals is scarce. Thus, this study aims to examine the impact of family and school in shaping readers relate what they read with what they see, what they feel, what they live, finally, that build social, historical and political meanings on reading the text in which they engage, becoming thus subject thinking, so that they learn to use their potential for thought in the construction and reconstruction of concepts to understand the world around them. To this end, we investigated the involvement of family and school in promoting literacy events with children with Down Syndrome. Developed a qualitative, cross-sectional study in which questionnaires to parents or guardians and educators to check promoting literacy situations were applied, and applied materials were analyzed and observed lessons in reading APAE. The research results show that three of the five mothers are semi-literate and do not read to their children, or have books at home. Two families have higher education and promote literacy events with children and adolescents with DS. Teachers conduct practices and literacy events observed in lessons and language workshop. The two students with Down syndrome whose families are literate understand, question, retell and dramatize texts; the three students whose families are not literate can understand and retell stories. In the lessons observed the teachers promote literacy events using various text genres. According to these observations, it seems possible to conclude that students with Down syndrome can achieve satisfactory levels of literacy when well guided by teachers committed to the work and even more if they have contact with materials written early with family.